If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + 8) + y = 2(y + 3) + -4 Reorder the terms: 3(8 + y) + y = 2(y + 3) + -4 (8 * 3 + y * 3) + y = 2(y + 3) + -4 (24 + 3y) + y = 2(y + 3) + -4 Combine like terms: 3y + y = 4y 24 + 4y = 2(y + 3) + -4 Reorder the terms: 24 + 4y = 2(3 + y) + -4 24 + 4y = (3 * 2 + y * 2) + -4 24 + 4y = (6 + 2y) + -4 Reorder the terms: 24 + 4y = 6 + -4 + 2y Combine like terms: 6 + -4 = 2 24 + 4y = 2 + 2y Solving 24 + 4y = 2 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 24 + 4y + -2y = 2 + 2y + -2y Combine like terms: 4y + -2y = 2y 24 + 2y = 2 + 2y + -2y Combine like terms: 2y + -2y = 0 24 + 2y = 2 + 0 24 + 2y = 2 Add '-24' to each side of the equation. 24 + -24 + 2y = 2 + -24 Combine like terms: 24 + -24 = 0 0 + 2y = 2 + -24 2y = 2 + -24 Combine like terms: 2 + -24 = -22 2y = -22 Divide each side by '2'. y = -11 Simplifying y = -11
| 34-x/8=x/9 | | 12-6/5b=5 | | 1/4t+35/12=109/36 | | -4k-9=-1 | | -5z+7z=5z-3+8z | | 100=(16+r)+r | | 3[-5x+5-3(x+1)]=-7x-4 | | 2d=28 | | -4x+6y=-24 | | .25x+.05(20-x)=.10(6) | | -12/7/(-4/11) | | 3x+28=8 | | -5(y-4)=-4y-8 | | 2/3+7/8*9/2 | | 2-80/15 | | -1/4X+48=-2X+6 | | Y^2+y=5 | | -5z+5+6z=12 | | I=per | | x-3/13=5/13 | | p+p+2p+(-3p)-7=0 | | 8/3x-2/3x | | 4/15/7/12 | | 14z=-12z+25z+7-2+6 | | 42x^3+36x^2+35x+30=0 | | 14z=-12z+25z | | -1/9-4/9 | | 4x+32=28 | | -4x+10+6x=26 | | r+7+4=2r-3 | | 525.00+0.21x=525.00 | | 4(-1+8)= |